2020
DOI: 10.3390/diagnostics10030171
|View full text |Cite
|
Sign up to set email alerts
|

GRB10 and E2F3 as Diagnostic Markers of Osteoarthritis and Their Correlation with Immune Infiltration

Abstract: This study aimed to find potential diagnostic markers for osteoarthritis (OA) and analyze the role of immune cells infiltration in this pathology. We used OA datasets from the Gene Expression Omnibus database. First, R software was used to identify differentially expressed genes (DEGs) and perform functional correlation analysis. Then least absolute shrinkage and selection operator (LASSO) logistic regression and support vector machine-recursive feature elimination algorithms were used to screen and verify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 45 publications
(50 reference statements)
0
82
0
Order By: Relevance
“…The upregulation of the suppressor of cytokine signaling 3 (SOCS3) gene increases the risk of AMI by potentiating inflammatory responses (16). Moreover, research has shown that immune cell infiltration plays an increasingly significant role in the occurrence and development of various diseases (11,(17)(18)(19). With regards to AMI, mast cells, M2 macrophages, and eosinophils have been demonstrated to affect cardiac function after AMI, providing novel insights into the significance of immune modulation in the infarcted heart (20).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulation of the suppressor of cytokine signaling 3 (SOCS3) gene increases the risk of AMI by potentiating inflammatory responses (16). Moreover, research has shown that immune cell infiltration plays an increasingly significant role in the occurrence and development of various diseases (11,(17)(18)(19). With regards to AMI, mast cells, M2 macrophages, and eosinophils have been demonstrated to affect cardiac function after AMI, providing novel insights into the significance of immune modulation in the infarcted heart (20).…”
Section: Introductionmentioning
confidence: 99%
“…CIBERSORT is a computational tool widely used in the analysis of immune responses of 22 types of immune cells under numerous diseases such as atopic dermatitis [ 11 ], lupus nephritis [ 12 ], ischemia-reperfusion injury in renal transplantation [ 13 ], osteoarthritis [ 14 , 15 ], in fresh, frozen and fixed specimens [ 16 ] based on microarray and RNA-seq data. However, only few researches have utilized the CIBERSORT method to investigate immune cell infiltration characteristics in acne and rosacea.…”
Section: Introductionmentioning
confidence: 99%
“…However, our research has some limitations. CIBERSORT analysis is based on limited genetic data, which may deviate from heterogeneous interactions between cells, disease-induced disorders, or phenotypic plasticity (Deng et al, 2020). Second, our sample size is relatively small, so the analysis of the results may not be powerful enough.…”
Section: Discussionmentioning
confidence: 99%
“…CIBER-SORT is a method for quantifying cell type composition from tissue gene expression datasets based on immune cell signatures (Newman et al, 2015). It has been widely used to analyze immune cell infiltration in various diseases such as osteoarthritis (Deng et al, 2020), colorectal cancer (Ye et al, 2019) and atherosclerosis (Xu and Yang, 2020). However, so far, there have been no reports on the use of CIBERSORT to analyze the infiltration of SS immune cells.…”
Section: Introductionmentioning
confidence: 99%